1976
DOI: 10.1161/01.res.39.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of plasma renin activity by indomethacin in man.

Abstract: SUMMARY The effect of indomethacin or placebo on aldosterone, plasma renin activity (PRA), sodium excretion, and urinary prostaglandin (PC) levels was investigated in five hypertensive subjects in 100 mEq sodium balance who had experienced malignant hypertension with a disturbance of their renin-aldosterooe relationship in the past. Indomethacin significantly lowered aldosterone levels by 43%, PRA by 58%, 24-bour sodium excretion by 49%, and urinary PC excretion, an indicator of renal PC synthesis, by 67%. Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
1
4

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(81 citation statements)
references
References 21 publications
10
66
1
4
Order By: Relevance
“…The ability of frusemide to stimulate the renin angiotensin system was evident from 5 min and reached maximum at 10 min which is consistent with previous reports (Frolich et al, 1976;Johnston et al, 1986;Mackay et al, 1984). The increases in renal plasma flow following frusemide have been reported before (Mackay et al, 1984) and are critically dependent on salt balance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ability of frusemide to stimulate the renin angiotensin system was evident from 5 min and reached maximum at 10 min which is consistent with previous reports (Frolich et al, 1976;Johnston et al, 1986;Mackay et al, 1984). The increases in renal plasma flow following frusemide have been reported before (Mackay et al, 1984) and are critically dependent on salt balance.…”
Section: Discussionsupporting
confidence: 91%
“…Frusemide causes acute increases in plasma renin activity (Frolich et al, 1976;Johnston et al, 1986) and prostaglandin excretion (Mackay et al, 1984). Captopril has previously been shown to inhibit the diuretic responses to frusemide in animals, and in dogs there is evidence that captopril abolishes the acute increases in renal blood flow produced by intravenous frusemide (Johnston et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Our study, therefore, lends support to previous reports which have advanced evidence that nonsteroidal anti-inflammatory agents result in sodium chloride retention (3)(4)(5). The fact that two structurally different nonsteroidal anti-inflammatory drugs had similar effects on chloride transport in each of the segments examined, is evidence against nonspecific, nonprostaglandin-mediated effects.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that nonsteroidal antiinflammatory drugs may promote salt retention (3)(4)(5). Furthermore, these agents are generally believed to act by inhibiting endogenous prostaglandin production.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition by prostaglandin synthetase inhibitors of the early increase in plasma renin activity in man (Frolich et al, 1976;Tan & Mulrow, 1977;Goldiner et al, 1981) has been confirmed in this study, although such an effect was only significant 5 and 40 min after frusemide. However there was a tendency towards lower levels of PRA at all times after frusemide suggesting that at least part of the mechanism determining renin release is prostaglandin dependent.…”
Section: Prostaglandins and Frusemide 517supporting
confidence: 76%